Pentraxin 3 in primary percutaneous coronary intervention for ST elevation myocardial infarction is associated with early irreversible myocardial damage: Kinetic profile, relationship to interleukin 6 and infarct size. Issue 4 (1st June 2020) - Butt, Noreen; Bache-Mathiesen, LK; Ushakova, A; Nordrehaug, JE; Jensen, SE; Munk, PS; Danchin, N; Dubois-Rande, JL; Hansen, HS; Paganelli, F; Corvoisier, P Le; Firat, H; et al.
Abstract : Background: The inflammatory marker long pentraxin 3 (PTX3) has been shown to be a strong predictor of 30-day and one-year mortality after acute myocardial infarction. The aim of this study was to evaluate the kinetic profile of PTX3 and its relationship with interleukin 6 (IL-6), high-sensitive C-reactive protein (hs-CRP) and infarct size. Methods: PTX3, IL-6 and hs-CRP were measured at predefined time points, at baseline (before percutaneous coronary intervention (PCI)), at 12 and 72 hours after PCI in 161 patients with first-time ST elevation myocardial infarction (STEMI). Results: PTX3 and IL-6 levels increased in the early phase, followed by a gradual decrease between 12 and 72 hours. There were statistically significant correlations between PTX3 and IL-6 in general, for all time points and for changes over time (0–72 hours). In a linear mixed model, PTX3 predicted IL-6 ( p  < 0.001). PTX3 is also correlated with hs-CRP in general, and at each time point post PCI, except at baseline. PTX3, IL-6 and hs-CRP were all significantly correlated with infarct size in general, and at the peak time point for maximum troponin I. In addition, there was a modest correlation between IL-6 levels at baseline and infarct size at 72 hours after PCI ( ρ  = 0.23, p  = 0.006). Conclusions: PTX3 had a similar kinetic profile to IL-6, with an early increase and decline, and was statistically significantly correlated with markers of infarct size in STEMI patients post primary PCI. Baseline levels of IL-6 only predicted infarct size at 72 hours post PCI.